2019
DOI: 10.3389/fchem.2019.00237
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Investigations Suggest a Non-specific Recognition Strategy of 14-3-3σ Protein by Tweezer: Implication for the Inhibition Mechanism

Abstract: The supramolecular complex formed between protein and designed molecule has become one of the most efficient ways to modify protein functions. As one of the more well-studied model systems, 14-3-3 family proteins play an important role in regulating intracellular signaling pathways via protein-protein interactions. In this work, we selected 14-3-3σ as the target protein. Molecular dynamics simulations and binding free energy calculations were applied to identify the possible binding sites and understand its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 90 publications
1
16
0
Order By: Relevance
“…Based on these studies, it can be concluded that tweezers can recognize more than one lysine residue of 14-3-3 proteins. Theoretical studies have also confirmed this finding ( Bier et al, 2013 ; Shi and Xu, 2019 ). The relative quantum mechanical (QM) energies have been evaluated via combined quantum mechanical and molecular mechanical (QM/MM) calculations, which indicated that in addition to K214, some other lysine residues (K87, K141, K160, and K195) could also be recognized by the tweezer ( Bier et al, 2013 ).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Based on these studies, it can be concluded that tweezers can recognize more than one lysine residue of 14-3-3 proteins. Theoretical studies have also confirmed this finding ( Bier et al, 2013 ; Shi and Xu, 2019 ). The relative quantum mechanical (QM) energies have been evaluated via combined quantum mechanical and molecular mechanical (QM/MM) calculations, which indicated that in addition to K214, some other lysine residues (K87, K141, K160, and K195) could also be recognized by the tweezer ( Bier et al, 2013 ).…”
Section: Introductionsupporting
confidence: 55%
“…The binding of tweezers to 14-3-3 proteins is a representative example of supramolecules regulating protein functions. Several experimental and theoretical studies have investigated the binding events between tweezers and 14-3-3 proteins ( Bier et al, 2013 ; Bier et al, 2017 ; Shi and Xu, 2019 ; Guillory et al, 2021 ). Via isothermal titration calorimetry (ITC), Bier et al found that tweezers exhibited at least two binding events with different affinities to 14-3-3σ ( Bier et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…S6, ESI†), which is widely applied in MD simulation. 65,88,89 A large range of RMSD values was found for the BRD4-BD1 systems, between 0.5 and 5.5 Å, due to the long C-terminal chain compared with that in BRD4-BD2. However, the RMSD of residues 61–166 (excluded the C-terminal) was 0.91 ± 1.12 Å (1.43 ± 1.86 Å for all length) in the 1000 ns MD simulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The MM/GBSA approach 63,64 is efficient to evaluate ligand and enzyme systems. 65–67 The MM/GBSA framework has previously been discussed; 68–70 hence, only a short description is provided here. The total binding free energy for the binding of NHWD-870 of BRD4-BD1 and BRD4-BD2, namely Δ G binding was determined as follows:Δ G binding = Δ G complex − Δ G protein − Δ G ligand G = E gas + G sol − TS E gas = E int + E vdW + E ele G sol = G el + G nonel Δ G complex , Δ G protein and Δ G ligand represent free energies of NHWD-870/BD1 or BD2 of BRD4, BD1 or BD2 of BRD4 and NHWD-870, respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The 14-3-3 protein belongs to a highly conserved acidic protein family prevalent in eukaryotic cells. It binds to more than 200 phosphorylated proteins and plays key roles in the regulation of cell mitosis, growth, differentiation, survival, apoptosis, migration and diffusion, thus affecting tumour formation (Aitken 2006, Cau et al 2018, Shi and Xu 2019. There are at least seven highly conserved subtypes of the 14-3-3 protein encoded by different genes in mammals: α/β, γ, ε, ζ, η, σ and θ/τ (Cau et al 2018, Hermeking 2003.…”
Section: Introductionmentioning
confidence: 99%